The somatic growth pattern of preterm infants until term age - Ida Bagus Andhita; Soetjianingsih Soetjianingsih; I. Wayan Retayasa (Paediatrica Indonesiana, 2009)
Background  Pre term infants contribute substantially to neonatalmorbidity  and  mortality rates. Somatic growth  is  consideredto be  an  important indicator  of  an  infant's health status.  Themeasurement parameters include body weight (BW), body length(BL), head circumference (HC), and ponderal index (PI). Specificdata  on  the somatic growth pattern  of  preterm infants in Indonesiaare unavailable.Objectives  To  identify the somatic  pattern  of  preterm infantsuntil term age  and  the influence  of  gender, nutrition, and nursingmethod  on  BW,  BL,  HC,  and  PI growth during the first week  oflife.Methods  We  recruited premature infants born in Sanglah Hopsital,Denpasar, Bali,  and  collected data  on  BW,  BL,  HC,  and  PI>All  data  were presented  as  mean (SD)  and  plotted in curves.The  relationships among several factors and the somatic growthparameters were analyzed with  ANOV  A.  The  level  of  significancewas set  at  P  <  0.05.Results  Among  100  infants, significant differences were detectedin  the  mean  ofBW,  BL,  HC, and PI, particularly in early preterminfants. Breastfed infants had the highest values with BW  2199grams (SD  198),  HC  31.4  em  (SD  1.71),  and PI  2.48  grams/cm 3(SD  0.36).  Infants nursed with the kangaroo method had thehighest values  of  BW  [2450  grams (SD  259)]  and  BL  [48  em(SD  2.34)].Conclusion  A significant difference was  detected  in somaticgrowth according to some parameters, particularly in the earlypreterm infants group. Thus, breast feeding and the kangaroomethod contribute to better somatic growth, and specifically BW.